Phonon-mediated high-temperature superconductivity in clathrate superhydride ThCeH18 under pressure - Prutthipong Tsuppayakorn-aek; Wei Luo; Thiti Bovornratanaraks (Scientific Reports)
Abstract Predicting high-temperature superconductivity in hydrogen-rich dense metallic states under pressure remains a significant challenge. The discovery of new phases of metal hydrides is vital for advancing this area of research. In our study, we present the superconducting phases of ThCeH18 using a search strategy based on potential energy surfaces and evolutionary algorithms under pressure. Consequently, ThCeH18 is thermodynamically stable in a crystalline hexagonal unit cell with the space group $$P\bar{6}m2$$ , similar to CeLaH18 and LaThH18. The critical importance of hydrogen atoms is demonstrated, showcasing their significant influence on the evolution of T c. Isotropic superconductivity in ThCeH18, driven by electron-phonon interactions and analyzed using the stochastic self-consistent harmonic approximation (SSCHA) to account for anharmonicity, reveals a strong anharmonic correction and strong electron-phonon coupling, resulting in high-temperature superconductivity with a T c of approximately 136 K at 50 GPa.This approach provides a promising direction for identifying new classes of superconducting materials and offers valuable insights into enhancing superconductivity through structural prediction.